Reassessing the taxonomy of the Libidibia ferrea complex, the iconic Brazilian tree “pau-ferro” using morphometrics and ecological niche modeling - Oliveira, Filipe G.; Santos, Felipe da S.; Lewis, Gwilym P.; de Oliveira, Reyjane P.; de Queiroz, Luciano P. (Revista brasileira de botânica, 2024)
Libidibia is a small genus of caesalpinioid legumes with seven species spanning from Mexico and the Caribbean to southern South America. Within this genus, Libidibia ferrea stands out as an iconic Brazilian tree currently classified into the varieties ferrea , glabrescens , leiostachya , and parvifolia . They comprise a species complex together with three other varieties currently accepted as synonyms (var. cearensis , var. megaphylla and var. petiolulata ). Together they exhibit complex morphological variation, along with confusion regarding their common names and geographic distribution. Five distinct morphotypes were recognized which were compared using a morphometric study of 26 quantitative leaf characters. We also performed ecological niche modeling for those morphotypes spanning from Quaternary to the present. Principal Component Analysis (PCA) and Discriminant Analysis (DA) revealed four main clusters which also present distinct niche preferences throughout the Quaternary and current distinct geographical distributions. Based on our findings, we propose recognizing four morphotypes as separate species: L. ferrea , L. juca , L. leiostachya , and L. parvifolia . Libidibia ferrea and L. juca are small trees and shrubs, distributed respectively in the southern portion of the ‘Caatinga’ and from the Amazon to the northern ‘Caatinga’ region. On the other hand, L. leiostachya and L. parvifolia are both tall trees, predominantly inhabiting the wetter regions of the ‘Caatinga’ ( L. parvifolia ) and extending into the coastal rainforests of southeastern Brazil ( L. leiostachya ). Three new combinations are proposed and an identification key, diagnostic descriptions, and taxonomic notes are presented.